2018
DOI: 10.18203/2319-2003.ijbcp20183033
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological adverse drug reactions in tertiary care hospital: an analysis of causality and severity

Abstract: Background: Dermatological adverse drug reactions (ADRs) are easily detected by patients and that precludes further usage of drugs. So, decided to study the pattern, causative drugs, severity of adverse drug reactions and their causality in tertiary care hospital.Methods: It was prospective non inventional cross sectional study. Patients attending OPD or admitted to IPD of all age group and both gender with suspected dermatological ADRs following drug intake were included and the ADRS were recorded on CDSCO’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Multiple medical problems may also increase the chance of developing ACDR. [ 12 ] In the causality assessment using WHO guidelines, there were 66 (9.1%) certain cases, 224 (30.83%) probable cases, and 436 (60%) possible cases, which is similar to Bharani et al ,[ 13 ] where out of 231 cases, 3 (1.3%) cases were classified certain, 68 (29.4%) cases as probable, and 160 (69.3%) cases as possible. In our study, Naranjo score showed 73 (10%) definite cases, 255 (35%) probable cases, and 400 (55%) possible cases, which was similar to Jadhav et al .…”
Section: Discussionsupporting
confidence: 73%
“…Multiple medical problems may also increase the chance of developing ACDR. [ 12 ] In the causality assessment using WHO guidelines, there were 66 (9.1%) certain cases, 224 (30.83%) probable cases, and 436 (60%) possible cases, which is similar to Bharani et al ,[ 13 ] where out of 231 cases, 3 (1.3%) cases were classified certain, 68 (29.4%) cases as probable, and 160 (69.3%) cases as possible. In our study, Naranjo score showed 73 (10%) definite cases, 255 (35%) probable cases, and 400 (55%) possible cases, which was similar to Jadhav et al .…”
Section: Discussionsupporting
confidence: 73%